2006
DOI: 10.1007/s00431-006-0168-2
|View full text |Cite
|
Sign up to set email alerts
|

Transumbilical embolization of hepatic arteriovenous malformation in a neonate with heart failure

Abstract: A newborn infant presented with severe heart failure due to a large hepatic arteriovenous malformation (AVM). Umbilical artery (UA) access was safely used for immediate diagnosis and for embolization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 6 publications
(5 reference statements)
0
11
0
Order By: Relevance
“…However, if catheterized, the artery will remain patent and can serve as vascular access for interventional procedures. 1 Once the umbilical artery is catheterized, a wire and a catheter can be passed into the anterior division of the iliac artery and then the aorta and eventually to the location of interest. 1 Although crucial to survival for many patients, umbilical vascular catheters are not without risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…However, if catheterized, the artery will remain patent and can serve as vascular access for interventional procedures. 1 Once the umbilical artery is catheterized, a wire and a catheter can be passed into the anterior division of the iliac artery and then the aorta and eventually to the location of interest. 1 Although crucial to survival for many patients, umbilical vascular catheters are not without risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for management of HAVM include supportive pharmacologic therapy of congestive heart failure with digoxin and diuretics, transcatheter embolization, surgical resection, and ligation, and, in cases of diffuse HAVM, possibly liver transplantation. [7][8][9][10][11] Surgical intervention is typically reserved for more simple and smaller HAVM which can be resected and has a high mortality risk in critically ill infants. The transarterial approach depending on HAVM composition can be a stop gap measure to curative.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical ligation of hepatic artery has also been described by some [22,24]. We used transcatheter approach through femoral artery for coil embolisation of AVM, though trans-umbilical approach has also been described by Costa and colleagues [17]. All of the studies have described acceptable results with the occlusion of AVM and resolution of the symptoms.…”
Section: Treatment Optionsmentioning
confidence: 99%
“…Retrospectively thinking, we believe that an AVM should be suspected in a patient who has relatively high systemic saturation for a single ventricle physiology, as in our first case. A keen review of the literature has also confirmed CHF as one of the main presenting feature in majority of the studies [12][13][14][15][16][17][18][19][20]. Other uncommon modes of presentation are portal hypertension [16,20,21], abdominal pain, mass, ischemia or distension [16,[19][20][21][22][23][24], primary pulmonary hypertension [25] and bleeding episodes [26].…”
Section: Diagnosing An Avmmentioning
confidence: 99%
See 1 more Smart Citation